1995
DOI: 10.1055/s-2007-979731
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Disability and Head Growth in Rett Syndrome - A Preliminary Report

Abstract: Growth of head circumference was measured in 99 RS girls and compared to gross motor function. The degree of head growth deceleration correlated to the severity of gross motor disability at 12 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…Interestingly however, weight for height ratio did not decline with age, although these data were available for only a small subset of the sample. Also, in line with previous findings, these growth characteristics showed marginally significant associations with the physical features of RS, including motor ability, oral motor difficulties, fixed deformities, and breathing abnormalities (Stenbom et al 1995).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly however, weight for height ratio did not decline with age, although these data were available for only a small subset of the sample. Also, in line with previous findings, these growth characteristics showed marginally significant associations with the physical features of RS, including motor ability, oral motor difficulties, fixed deformities, and breathing abnormalities (Stenbom et al 1995).…”
Section: Discussionsupporting
confidence: 90%
“…In common with previous studies, in the subsample for which growth characteristics were available, a significant proportion of the individuals with RS were of low weight and height and had smaller head circumferences. Further, the growth of these individuals decelerated in comparison with population norms with increasing age, such that by adulthood, almost all individuals were of low or extremely low weight, height and head circumference (Coleman et al 1988, Stenbom et al 1995. Interestingly however, weight for height ratio did not decline with age, although these data were available for only a small subset of the sample.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous preliminary report on head growth in RS, we showed that at 12 y of age, there was a significant and successive deceleration with increasing gross motor disability (8). In the present study, we studied OFC longitudinally in girls within the Swedish RS register series with classic or forme fruste types.…”
mentioning
confidence: 67%
“…The reduced head circumference in Rett syndrome, which has been correlated with the degree of motor handicap [Stenbom et al, 1995;Hagberg et al, 2000] Casanova et al [1991] and Murakami et al [1992] reported a global hypoplasia of the brain by magnetic resonance imaging. Reiss et al [1993] and Subramajiam et al [1997] reported a significant reduction in grey matter throughout the cortex with greater reduction in prefrontal, posterior frontal, and anterior temporal regions.…”
mentioning
confidence: 99%